Предмет: Алгебра, автор: terp1mo

ПОМОГИТЕ РЕШИТЬ ПОЖАЛУЙСТА

Приложения:

Ответы

Автор ответа: 7x8
2

Ответ:

17

1\frac{1}{125}

Объяснение:

2^{-2}\cdot4^3+(5^{-7}\cdot(5^{-2})^{-3})^{-1}-2^2=\\\\2^{-2}\cdot (2^2)^3+(5^{-7}\cdot(5^{-6})^{-1}-4=\\\\2^{-2}\cdot 2^6+(5^{-1})^{-1}-4=\\\\2^{4}+5^{1}-4=16+5-4=21-4=17

3^{-4}\cdot 9^2\cdot 3^0+5^{-2}\cdot(0,2)^{-2}\cdot (5)^{-3}=\\\\3^{-4}\cdot (3^2)^2\cdot 1+5^{-2}\cdot(\frac{1}{5})^{-2}\cdot (5)^{-3}=\\\\3^{-4}\cdot 3^4+5^{-2}\cdot 5^{2}\cdot (5)^{-3}=\\\\3^0+5^{-3}=1+\frac{1}{5^3}=1+\frac{1}{125}=1\frac{1}{125}

Похожие вопросы
Предмет: История, автор: vadimlogunov26